Bunga rampai pemikiran Islam / Muhammad Ismail, penerjemah, Nurkhalis ; penyunting, A.R. Nasser, A. saefullah - ISMAIL, Muhammad; Nurkhalis; Nasser, A.R; Saefullah, A (Gema Insani Press, 1993)
198 hlm. ; 18 cm